2015
DOI: 10.1080/21645515.2015.1012010
|View full text |Cite
|
Sign up to set email alerts
|

Phase II studies to select the formulation of a multivalent HPV L1 virus-like particle (VLP) vaccine

Abstract: Our objective was to develop a multivalent prophylactic HPV vaccine that protects against infection and disease caused by HPV16/18 (oncogenic types in existing prophylactic vaccines) plus additional oncogenic types by conducting 3 Phase II studies comparing the immunogenicity (i.e., anti-HPV6/11/16/18 geometric mean titers [GMT]) and safety of 7 vaccine candidates with the licensed quadrivalent HPV6/11/16/18 vaccine (qHPV vaccine) in young women ages 16-26. In the first study (Study 1), subjects received one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…[19][20][21] Similarly, antigen concentrations for HPV types 6, 16 and 18 needed to be increased in the 9-valent HPV vaccine in comparison to the concentrations found in 4-valent HPV vaccine. 22 Dose ranging studies for PCV7 and PCV9 were only conducted in older adults in order to determine whether the pediatric dose level of these vaccines were sufficiently immunogenic in older adults or if a higher dose was required; dosedependent response was observed when comparing 1x, 2x, and 4x doses of PCV7 but highest dose was associated with more adverse events. 23,24 Although our initial formulation of PCV15 induced both IgG and OPA antibodies to all 15 serotypes included in the vaccine in both adults and infants, levels of serotype-specific antibodies measured following the third dose infant series (1 month PD3) were generally lower to those measured in infants vaccinated with PCV13 for 12 out of 13 shared serotypes between the 2 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Similarly, antigen concentrations for HPV types 6, 16 and 18 needed to be increased in the 9-valent HPV vaccine in comparison to the concentrations found in 4-valent HPV vaccine. 22 Dose ranging studies for PCV7 and PCV9 were only conducted in older adults in order to determine whether the pediatric dose level of these vaccines were sufficiently immunogenic in older adults or if a higher dose was required; dosedependent response was observed when comparing 1x, 2x, and 4x doses of PCV7 but highest dose was associated with more adverse events. 23,24 Although our initial formulation of PCV15 induced both IgG and OPA antibodies to all 15 serotypes included in the vaccine in both adults and infants, levels of serotype-specific antibodies measured following the third dose infant series (1 month PD3) were generally lower to those measured in infants vaccinated with PCV13 for 12 out of 13 shared serotypes between the 2 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…All participants who received ≥1 study vaccination and had follow-up data are included in the analysis of safety with the following exceptions: (1) subjects enrolled in the dose-selection portion of study 001 who received 9vHPV vaccine dose formulations not selected for Phase III evaluation, that is, lowdose and high-dose 9vHPV vaccine (previously reported) 15,16 ; (2) subjects randomized to the saline placebo arm of study 006 (previously reported; n = 306) 12 ; and (3) a small number of subjects (<0.1%) who accidentally received noncompliant dosing regimens (eg, mixed regimens of 9vHPV and qHPV vaccine or mixed regimen of 9vHPV vaccine and placebo). This combined analysis of safety data provides a cross-study summary of AEs and new medical conditions, described as frequencies and percentages across study group and type of event.…”
Section: Discussionmentioning
confidence: 99%
“…Most subjects (97.2%; 15 427 of 15 875) received the 3 vaccinations. a Subjects who received the low-dose or high-dose formulation of 9vHPV vaccine during the dose selection portion of the study 8,15 are not considered in this report; safety fi ndings in these subjects are reported in Luxembourg et al 16 b Visit cutoff date: March 10, 2014; maximum follow-up 72 mo after vaccination dose 1 (median: 48 mo). c Subjects who received placebo in Study 006 are not considered in this report; safety fi ndings in these subjects are reported.…”
Section: Vaccinationmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] Clinical trials have now established the safety, efficacy and immunogenicity of a three dose schedule of a nonavalent HPV vaccine, whose composition is based on the VLP and vaccine production methods underpinning the quadrivalent vaccine with higher HPV16/18/6 VLP concentrations, more adjuvant and inclusion of the next five most commonly detected oncogenic HPV types in cervical cancers (types 31,33,45,52,58). [38][39][40] For ethical reasons, the control group in the vaccine trial was given the quadrivalent vaccine rather than a placebo. The nonavalent vaccine provided equivalent antibody titres against HPV16/18/6/11 as the quadrivalent vaccine at month 7 and recipients had an equivalent incidence of 6/11/16/18-related infection and high grade cervical disease (CIN21) rates.…”
Section: Current Knowledge About the Efficacy And Safety Of Prophylacmentioning
confidence: 99%